2023
DOI: 10.3345/cep.2023.00353
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nonalcoholic fatty liver disease and hyperandrogenemia in adolescents with polycystic ovary syndrome

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is common in adults with polycystic ovary syndrome (PCOS), and several studies on adults have investigated its influencing factors. However, factors associated with NAFLD in adolescents with PCOS remain unknown.Purpose: This study aimed to investigate the presence of NAFLD in adolescents with PCOS using the noninvasive methods of vibration-controlled transient elastography (VCTE) and ultrasonography (USG), along with assessing NAFLD-related metabolic and hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…PCOS and NAFLD share similar clinical presentations, including central obesity and metabolic abnormality [39,40], and a well-known association between NAFLD and IR in PCOS has been described by numerous authors [9,10,41]. Nevertheless, consistent with our ndings, Tantanavipas et al [42], after multivariate logistic regression, reported that the association between NAFLD and IR in PCOS did not persist and suggested that hyperandrogenism, rather than IR, plays a pivotal role in the onset of hepatic fat deposition in PCOS, as previously reported by other studies [10,37,43]. Such an association between NAFLD and androgens was corroborated by a meta-analysis of 17 studies, which revealed that only hyperandrogenic PCOS patients had a signi cantly higher risk of NAFLD than the controls (OR = 3.31, 95% CI = 2.58-4.24), leading to the conclusion that NAFLD screening should be warranted for PCOS patients only in the presence of hyperandrogenism [44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…PCOS and NAFLD share similar clinical presentations, including central obesity and metabolic abnormality [39,40], and a well-known association between NAFLD and IR in PCOS has been described by numerous authors [9,10,41]. Nevertheless, consistent with our ndings, Tantanavipas et al [42], after multivariate logistic regression, reported that the association between NAFLD and IR in PCOS did not persist and suggested that hyperandrogenism, rather than IR, plays a pivotal role in the onset of hepatic fat deposition in PCOS, as previously reported by other studies [10,37,43]. Such an association between NAFLD and androgens was corroborated by a meta-analysis of 17 studies, which revealed that only hyperandrogenic PCOS patients had a signi cantly higher risk of NAFLD than the controls (OR = 3.31, 95% CI = 2.58-4.24), leading to the conclusion that NAFLD screening should be warranted for PCOS patients only in the presence of hyperandrogenism [44].…”
Section: Discussionsupporting
confidence: 90%
“…Supported by some studies on PCOS, we found a higher prevalence of hepatic steatosis in the PCOS group [36,37] and a positive association between TE-CAP values and triglyceride levels [36, 38], although such a correlation was borderline in our study. PCOS and NAFLD share similar clinical presentations, including central obesity and metabolic abnormality [39,40], and a well-known association between NAFLD and IR in PCOS has been described by numerous authors [9,10,41].…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of NAFLD has been reported to be either not different or higher in prevalence in adolescent and adult individuals with PCOS, and it has been associated with higher rates of obesity, insulin-resistance, hypertriglyceridemia, and hyperandrogenemia indices. 103 , 104 , 105 , 106 , 107 NAFLD also is associated with an increased transition and incidence of type 2 diabetes in the general population and in those with PCOS. 108 The 4.27% prevalence of NAFLD in those with PCOS in our results is very low compared to findings in other population cohort studies, which show a 40%-50% prevalence in those with PCOS.…”
Section: Discussionmentioning
confidence: 99%